Variable repeats in the eukaryotic polyubiquitin gene ubi4 modulate proteostasis and stress survival - Rita Gemayel (Nature Portfolio, 2017)
Eukaryotic cells rely on the ubiquitin-proteasome system for selective degradation of proteins, a process vital to organismal fitness. Here the authors show that the number of repeats in the polyubiquitin gene is evolutionarily unstable within and between yeast species, and that this variability may tune the cell’s capacity to respond to sudden environmental perturbations.